Sofia Ivanovna Karamazova, Shrieker: The Formation of an Individual Self from a Collective Identity - Dossi, Giulia (Wiener Slawistischer Almanach, 2023)
In this paper, I examine how A. I. Klementovskii in “Klikushi” (“Shriekers,”1860), and I. G. Pryzhov in “Russkie klikushi” (“Russian Shriekers,” 1868), while aimingto give medical and historical legitimacy to the phenomenon of klikushestvo (a Russianform of religious hysteria), create a collective identity for the women who suffered fromthis illness: the shriekers. I then consider how Dostoevskii used the collective identitythat emerged in Klementovskii’s and Pryzhov’s text to create his own shrieker character,Sofia Ivanovna Karamazova. In the figure of Sofia Ivanovna, Dostoevskii individualizedand transformed the medicalized trope of the shrieker, mixing it with elementsof Christian martyrdom, and in so doing he makes Sofia Ivanovna central to the developmentof “active love” in Alyosha’s character.